Spray doping method to create a low-profile high-density carbon nanotube thermoelectric generator. (January 2016) - Montgomery, David S.; Hewitt, Corey A.; Barbalace, Ryan; Jones, Travis; Carroll, David L.
Abstract: A new spray doping method is presented that allows for easily tunable thermoelectric properties of thin film carbon nanotube (CNT) polymer composites. An airbrush introduces small molecule Polyethyleneimine into existing p-type CNT films converting it to an n-type composite. This technique allows for the conversion of a single p-type film into a multi-section device of alternating p- and n-type segments. A thermoelectric generator (TEG) design is presented with the effort to address current design issues facing thin film thermoelectric devices as a commercially viable TEG. The Seebeck coefficient and electrical conductivity were tested under different dopant concentrations and compared with traditional solution based methods.